Influence of Oxynitrided Surface in the Production of a Less Susceptible Titanium Surface to Skin‐Borne Bacterial Adhesion. Issue 5 (27th November 2015) - Aires, Michelle de Medeiros; Treter, Janine; Braz, Danilo Cavalcante; Krug, Cristiano; Macedo, Alexandre José; Alves Júnior, Clodomiro
Abstract: There is a growing quest for an ideal biomaterial that shows appropriate cellular response and is not susceptible to microbial adhesion. In this study, commercial grade II titanium was submitted to RF/DC plasma surface modification at 2.2 mbar, using gas mixtures of argon, nitrogen, and oxygen at proportions 4:1:2 and 4:1:3. The surfaces were physically and chemically characterized. In order to evaluate bacterial response, the surfaces were exposed to S taphylococcus epidermidis . Oxynitrided samples, although having a higher roughness as compared with untreated samples, exhibited lower bacterial growth. This observation is probably due to the formation of different crystalline phases of nitrides and oxides caused by plasma treatment. The surface with highest contact angle and highest surface tension showed lower bacterial adhesion. These results were confirmed by scanning electron microscopy. The role of nitrogen in reducing bacterial adhesion is clear when this material is compared with untreated titanium, on which only an oxide film is present.